Difficulty Accessing Drinking Water during COVID-19 Pandemic in Indonesia - Zahra Zahra; Basuki Rahmat; Ika Dharmayanti; Tities Puspita; Alfons Letelay; Feri Ahmadi (Postgraduate, University of Mataram, 2023)
The problem of the availability of clean and safe water in Indonesia has increased during global climate change. The conditions of the COVID-19 pandemic also have an impact on increasing domestic water use. This study aims to assess drinking water access in household during COVID-19 pandemic. This study using data of National Household of Drinking Water Quality Survey. The survey conducted in 2020 of 21,829 household in Indonesia. Many households have increased water consumption, households for hand washing (49.6% HH), personal hygiene (37.2% HH), clean house (29.2% HH), and washing (33.9% HH). There are only 1.6% of HH have difficulty accessing drinking water source, 1.3% in urban area and 2.0% in rural area. The cause is 76.1% because of decreased water flow and 42.1% because of economic problems. Drinking water sources used by household who has difficulty accessing drinking water are piped water (26.8%), refill water (16.8%), and bore hole (13.6%). Only few of household difficult to access drinking water during COVID-19 pandemic, meanwhile there are increasingly of drinking water needs. It is suggested that the municipal government form a public-private partnership (PPP) to invest in immediate and long-term water infrastructure in order to strengthen the resilience of drinking water systems against future pandemics.